2020
DOI: 10.2196/17406
|View full text |Cite
|
Sign up to set email alerts
|

User-Centered Design and Evaluation of a Web-Based Decision Aid for Older Adults Living With Mild Cognitive Impairment and Their Health Care Providers: Mixed Methods Study

Abstract: Background Mild cognitive impairment (MCI) is often considered a transitional state between normal and pathologic (eg, dementia) cognitive aging. Although its prognosis varies largely, the diagnosis carries the risk of causing uncertainty and overtreatment of older adults with MCI who may never progress to dementia. Decision aids help people become better informed and more involved in decision making by providing evidence-based information about options and possible outcomes and by assisting them i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 55 publications
2
14
0
1
Order By: Relevance
“…The first subtheme, “ability to use the interface”, focused on the difficulties encountered while using the touchscreen, patience of using new technologies, and memory loss. These findings are consistent with those of Bogza et al [ 38 ], who observed that difficulties encountered while navigating technologies resulted in frustration in decision making. Hence, the information presented to persons with CI has to be meaningful, concise, and easy to remember.…”
Section: Discussionsupporting
confidence: 92%
“…The first subtheme, “ability to use the interface”, focused on the difficulties encountered while using the touchscreen, patience of using new technologies, and memory loss. These findings are consistent with those of Bogza et al [ 38 ], who observed that difficulties encountered while navigating technologies resulted in frustration in decision making. Hence, the information presented to persons with CI has to be meaningful, concise, and easy to remember.…”
Section: Discussionsupporting
confidence: 92%
“…First, in many studies, authors reflected on possible biases that might arise when using questionnaires to develop eHealth [ 24 , 69 , 80 , 97 , 109 , 115 , 126 , 134 , 138 , 139 , 142 , 146 , 149 ]. Among other things, vulnerable target groups with low literacy skills and no internet access were often hard to include in questionnaires [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that experts on, for example, usability or persuasive design can be included by means of cognitive walkthroughs or heuristic evaluations, whereas users can be involved through think-aloud procedures, guided by scenarios [ 127 ]. Second, authors stated that ideally, multiple methods should be combined to paint a full picture of a prototype’s usability [ 24 , 25 , 64 , 77 , 80 , 118 , 152 ]; for example, qualitative methods such as think-aloud procedures and interviews can be combined. Qualitative approaches can also be combined with quantitative data collected by means of, for example, log data analyses, questionnaire data, or eye tracking [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior research, as well as our own results, indicate that flexibility in program delivery is a necessary characteristic for successful technology training programs, as they allow for goal-motivated learning and individualization to accommodate participants' needs and abilities ( 31 ). To ensure flexibility and improve suitability and acceptance, programs can incorporate the end user throughout program design and development ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%